Outcomes in Symptomatic Patients With Vertebrobasilar Dolichoectasia Following Endovascular Treatment - Wang, Jiejun; Jia, Luqiong; Yang, Xinjian; Jia, Xuecang; Liu, Jian; Liu, Peng; Miao, Zefeng; Zhang, Ying; Tian, Zhongbin; Wang, Kun; Wang, Zhongxiao; Zhang, Yisen; et al. (Frontiers in Neurology, 2019)
Objective To evaluate whether the presenting symptoms of VBD predict the outcome of endovascular treatment. Methods We retrospectively reviewed our institutional clinical database and identified 22 patients (all males; mean age 52.6 years, range 11–73 years) with a diagnosis of VBD who underwent endovascular treatment from January 2010 to December 2017. Results After analyzing the clinical and imaging data, 22 symptomatic patients with VBD were assessed. At the time of VBD diagnosis, 13 patients (59%) had compressive symptoms, four (18%) had hemorrhagic symptoms, and five (23%) had ischemic symptoms. Nine of the total 22 patients (41%) who presented with hemorrhagic and ischemic symptoms achieved a satisfactory clinical and/or digital subtraction angiography imaging outcome after endovascular treatment. However, of the 13 patients who presented with compressive symptoms, seven (54%, 7/13) died from severe brainstem compression during follow-up; furthermore, MRI showed worsening of the mass effect in eight patients with compressive symptoms (62%, 8/13). Conclusions VBD is regarded a challenging lesion without an ideal treatment modality. However, the long-term outcome of endovascular treatment may be superior in patients with non-compressive symptoms compared with those with compressive symptoms.